Reflections on e-Learning readiness in Albanian education - Ezmolda Barolli; Kozeta Sevrani (Contemporary Economics, 2009)
Nowadays e-Learning has been identified to be the future of learning worldwide since the very powerful platform of the Internet has accelerated the speed of communication. Adoption of e-learning has become the latest trend across universities all over the world. Albania is part of a global shift from material resources to knowledge and intellectual resources as the basis for economic growth. Educators across Albania are aware that students must have an education that enables the students to participate successfully in and contribute to the knowledge economy. E-Learning readiness is an initial part of e-Learning development. In order to benefit from e-learning, higher education institutions in Albania should conduct considerable up-front analysis to assess their readiness. In this paper we are trying to examine the status of e-Learning readiness in Albania, analyzing and discussing several components and criteria based on literature.
Keywords: 330